En skildring av sex gymnasiekuratorers erfarenheter och arbete med elever med social fobi - Wennerström,Jenny (2007)
The purpose of this essay was to examine six high school welfare officers' experiences and work with students suffering from social phobia and discuss the welfare officers' view on social phobia from a psychiatric, cognitive and a knowledge theory. The study consists of qualitative interviews with welfare officers from several different high schools and attempts to answer the following questions: What previous experiences do welfare officers have of students with social phobia? How do welfare officers become aware of students with symptoms of social phobia and bring forth their problems? How do welfare officers describe their social work with students suffering from social phobia? The welfare officers' experiences of students with social phobia varied but turned out to be less salient than the amount of research in the area would suggest. The theoretical knowledge also varied, as did the acquiring and use of theory. These findings were then analysed on the basis of Rosmari Eliassons thoughts on knowledge, leading to the conclusion that the interviewed welfare officers do not construct their work on praxis-knowledge. The study's results concerning students with social phobia and the welfare officers' work with these students consisted in both deviant and common understandings, which were thereafter analysed according to cognitive theory. The predominant opinion among the welfare officers is that introvert students are given fairly high attention. Suspicion of social phobia arises when there is a significant decrease in a student's school results and attendance, when the student has a small social network, an isolating behaviour or experiences difficulties in different social contexts. These indicators can often lead to the recognition of the problem of social phobia, which is usually made by the teacher, the parents or even by the student himself or herself. There is little work done to prevent these problems and the counsellors'main working method consists of individual conversations with focus on the student's eneral situation. Establishing contact with the student, questions of integrity, waiting times at a referral, as well as making time for conversations are some of the difficulties encountered by welfare officers in their work with students with social phobia. The cooperation at school and with parents seems to work well; however, problems may arise due to professional secrecy of different authorities that may affect the understanding and insight of the other's work.
Keywords: skolkurator; social fobi; kognitiv teori; Social sciences; Samhällsvetenskaper; Social psychology; Socialpsykologi